2002
DOI: 10.1038/sj.onc.1205272
|View full text |Cite
|
Sign up to set email alerts
|

Activation of caspase-3 and cleavage of Rb are associated with p16-mediated apoptosis in human non-small cell lung cancer cells

Abstract: The p16 tumor suppressor gene is frequently inactivated in human cancer tissues and cell lines. We previously reported that wild-type p16 expression from an adenovirus vector (Adv/p16) induced p53-dependent apoptotic cell death in non-small cell lung cancer (NSCLC) cell lines. Here we show the potential mechanism of apoptosis induced by Adv/p16 infection. Infection of human NSCLC cell line A549, which carries the wild-type p53 gene, with Adv/p16 resulted in activation of caspase-3, accompanied by the cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 44 publications
5
32
0
Order By: Relevance
“…Cleavage of pRb was proposed to promote apoptosis via the release of E2F-1 from cleaved pRbs. 37,43 Nevertheless, the p68Rb-truncated form keeps the domain of interaction with E2F-1 and, in agreement, we found that p68Rb interacts with E2F-1 upon ABT-737 treatment. As caspase activity is required to upregulate Noxa and as a siRNA-targeting pRb expression impedes the induction of Noxa, we propose that p68Rb has an active role in the E2F-1 upregulation of Noxa (Supplementary Figure S4).…”
Section: Discussionsupporting
confidence: 87%
“…Cleavage of pRb was proposed to promote apoptosis via the release of E2F-1 from cleaved pRbs. 37,43 Nevertheless, the p68Rb-truncated form keeps the domain of interaction with E2F-1 and, in agreement, we found that p68Rb interacts with E2F-1 upon ABT-737 treatment. As caspase activity is required to upregulate Noxa and as a siRNA-targeting pRb expression impedes the induction of Noxa, we propose that p68Rb has an active role in the E2F-1 upregulation of Noxa (Supplementary Figure S4).…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, Cdk2 cleavage was specific to p53-expressing (Pin1 þ /À and Pin1À/À) thymocytes, and the level of cyclin A1 was significantly increased by g-ray irradiation in p53À/À and Pin1À/Àp53À/À thymocytes. Rb is one of the substrates of the Cdks, and is also cleaved by p27 Kip1 during apoptosis (Fattman et al, 1997;Katsuda et al, 2002). Although Rb was cleaved and was undetectable in the g-ray-irradiated Pin1 þ /À and Pin1À/À thymocytes, the hyper-phosphorylated form (Hyper-p-Rb) was detected in the g-ray-irradiated p53À/À and Pin1À/Àp53À/À thymocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In order to examine the effects of Pin1 and p53 deficiency on the sensitivity of thymocytes to DNA damage, primary cultured thymocytes were irradiated with 5 Gy of g-ray irradiation. Both Pin1 þ /Àp53 þ /À and Pin1À/Àp53 þ /À thymocytes showed apoptotic responses, including DNA ladder formation, caspase-3 activation, and fragmentation of RB and p27 Kip1 (Fattman et al, 1997;Loubat et al, 1999;Katsuda et al, 2002). In contrast, Pin1 þ /Àp53À/À and Pin1À/À p53À/À thymocytes showed lower sensitivities to g-rays, and caspase-3 activation and fragmentation of its substrate molecules were not observed.…”
Section: Discussionmentioning
confidence: 97%
“…Other groups using similar approaches in different cells have also detected p16-induced cell death ( [17][18][19][20][21] , reviewed in Calbó and Mazo 16 ), but the molecular mechanisms remain unclear. It has been proposed that p16 expression results in p53-dependent apoptosis, 17,18 but lack of wt-p53 gene in NP-18 cells makes this unlikely. It has also been described that p16 induces downregulation of Bcl-2, 17 but we did not detect changes in Bcl-2 or Bax expression following p16 expression in NP-18 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…p16-induced apoptosis resulted from the activation of p53-dependent apoptotic pathways ( [17][18][19][20][21] , reviewed in Calbó and Mazo 16 ), including bcl-2 downregulation and activation of caspases in non-small-cell lung cancer cells. 17,18 Interestingly, ectopic expression of p16 also induced apoptosis in p53-deficient cell lines, implicating a p53-independent apoptotic pathway. 20 Taken together, these results indicate that the effects of p16 on tumor cells depend on the genetic alterations acquired during transformation and tumor progression.…”
Section: Introduction P16mentioning
confidence: 99%